The Profile of Students’ Self-Efficacy in Using Chemdroid Media in Thermochemistry Topics - Febrian Solikhin; Andang Wijanarko (Journal of Educational Chemistry (JEC), 2021)
Self-efficacy is one of the factors that affect learning achievement. This study has the aim of analyzing the self-efficacy profile of students in learning using Chemdroid (Chemistry on Android) media. This media is an android-based media for Thermochemical material. This research is descriptive research with a quantitative approach. The classes used in this study were 2 classes with 60 students. Both are randomly selected. The first class is the control class (C-Class) which carries out hybrid learning, as usual, namely face-to-face in class and online learning using WhatsApp groups. The second class is the experimental class (E-Class) with face-to-face in class and using Chemdroid media. The learning time and the teacher in this study were the same. The instrument used is a self-efficacy measuring instrument consisting of 3 main aspects with 22 statements adapted from previous research. The results of the study were then analyzed and categorized into 5 categories. The results obtained indicate that the profile of students’ self-efficacy of E-Class students is higher than other class.